Environmental effects on the spatio‐temporal patterns of abundance and distribution of Sardina pilchardus and sardinella off the Mauritanian coast (North‐West Africa). (25th November 2016) - Bacha, Mahmoud; Jeyid, Mohamed Ahmed; Vantrepotte, Vincent; Dessailly, David; Amara, Rachid
Abstract: From 1998 to 2011, the effects of environmental conditions on the spatial and temporal trends of sardine and sardinella catch rates in the Mauritanian waters were investigated using generalized additive models. Two models were used: a global model and an oceanographic model. The global models explained more of the variability in catch rates (60.4% for sardine and 40% for sardinella) than the oceanographic models (42% for sardine and 32.4% for sardinella). Both species showed clear and inverse seasonal variations in abundances corresponding to their main spawning activities and the hydrologic seasons off the Mauritanian waters. Sardine prefer colder waters and seem to occupy the 'gap' in the northern part of the Mauritanian waters as soon as sardinella has left the area because of to lower water temperatures. Unlike sardinella, sardine showed a gradual southward extension between 2002 and 2009. The oceanographic model revealed that a high proportion of catch variability for the two species could be explained by environmental variables. The main environmental parameters explaining the variability are sea surface temperature (SST) and the upwelling index for sardinella, and the chlorophyll‐ a ( Chl‐a ) concentration, the upwelling index and SST for sardine. The sardinella spatio‐temporal variations off Mauritania seem to be more controlled by thermal than productivity gradients, probably linked to the species physiological constraints (thermal tolerance) whereas sardine seems to be more controlled by an 'optimal upwelling and temperature' windows. The results presented herein may be useful for understanding the movement of these species along the Mauritanian coast and hence their management under a changing climate.